Public-private partnership model for transport sector - Sreenath, Sreenivasan (2016)
The selection of the right Public- Private Partnership (PPP) model is an important policy decision of Governments during the feasibility phase of the PPP project. This is essential for attracting investors, achieving maximum value for money, timely financial closure and successful completion of the whole life cycle of the asset.